PENGARUH MODEL PEMBELAJARAN LEARNING CYCLE-5E BERORIENTASI SSI TERHADAP PENGETAHUAN EPISTEMIK - Vindhy Dian Indah Pratika; Faudina Permatasari (Al-Ihda' : Jurnal Pendidikan dan Pemikiran, 2024)
21st century education aims to improve students' scientific literacy skills. Scientific literacy is important for students so that they not only understand science as a concept but can also apply science in everyday life. This research aims to determine the effect of the SSI-oriented Learning Cycle 5E model on epistemic knowledge. The results of the research showed that experimental class II students obtained an average score for working on questions of 6.97, then the average score for experimental class I was 5.92 and the average score in the control class was 4.19. Thus, it shows that the SSI-oriented Learning Cycle 5E model has a better impact on learning compared to the two models used, namely Learning Cycle-5E and the direct learning method.